2002
DOI: 10.1093/milmed/167.11.923
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Sustained-Release Bupropion and Behavior Therapy for Tobacco Dependence in a Clinical Setting

Abstract: Despite decades of public education, cigarette smoking remains a serious health problem. The treatment approach at Tripler Army Medical Center is a unique collaboration of family practice physicians and health psychologists providing combination therapy to patients attempting to quit smoking. This article discusses a program evaluation of the Tripler Army Medical Center smoking cessation program. Patients attempting to quit smoking were assisted with a combination of cognitive-behavioral group therapy and sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…The third report is from the Tripler Army Medical Center in USA involving primary care physicians and health psychologists (21). Smokers received bupropion SR for 10 weeks along with group cognitive‐behavioural therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The third report is from the Tripler Army Medical Center in USA involving primary care physicians and health psychologists (21). Smokers received bupropion SR for 10 weeks along with group cognitive‐behavioural therapy.…”
Section: Resultsmentioning
confidence: 99%
“…114 More men than women quit with combined cognitive/behavioral group therapy and sustained release bupropion. 115 Quitting smoking has been reported to be harder for women than men, partially because of concern of the perceived potential for weight gain if they quit. 112,113 Other reasons that women may have a more difficult time in quitting include NRTs (especially gum and patches) may not be as effective in women, the medications to aid smoking cessation are not recommended for pregnant women, the menstrual cycle affects tobacco withdrawal symptoms and response to antismoking drugs vary by cycle phase, husbands provide less effective support to women than women give to men, women may be more susceptible to environmental cues (such as friends and moods) associated with the smoking ritual, and some women may enjoy the feeling of control associated with smoking.…”
Section: Womenmentioning
confidence: 99%
“…[100] Some studies, however, recommend NRT as the first line therapy for smoking cessation because of the amphetaminelike nature of bupropion, with some structural similarities, and similar side effects such as suppression of appetite, insomnia, weight loss and hypertension. [101] But several other studies claim that bupropion is a safe and efficacious drug [97,[102][103][104] and should be prescribed with consideration, especially to patients with hypertension. Study on selfadministered treatment for smoking cessation revealed that self-help manuals do increase quit rates when combined with individualised adjuncts such as written feedback and telephonic counselling.…”
Section: Resultsmentioning
confidence: 99%